(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to measure the holistic thinking of Arabic language teachers in the intermediate stage, due to the importance of holistic thinking and its connection to the current educational reality. To achieve this, a sample of 24 teachers in the city of Babylon for the academic year 2022-2023 who are teaching Arabic were chosen randomly. The researcher adopted the scale of holistic thinking by Al-Rawi (2019) and included 24 items to collect the needed data. The results revealed that Arabic language teachers have holistic thinking. There is no statistically significant difference in holistic thinking according to gender or service